Dosimetric Evaluation of the Sensitivity of PAGAT Gel Dosimeters Infused with Clinically Used Gadolinium-Based Contrast Agents - Melani Fuentealba; Carolina Vallejos; Sergio Díez; Mauricio Santibáñez (Gels)
This study evaluates the impact of gadolinium-based contrast agents (Omniscan, Dotarem, and Gadovist) on the performance of PAGAT gel dosimeters using spectrophotometric analysis. Dosimeters were infused with gadolinium at concentrations ranging from 0 to 40 mg/mL and irradiated with a 6 MV photon beam over a dose range of 0–15 Gy. Regarding dosimeter behavior, Dotarem exhibited an enhancement in optical density prior to irradiation due to polymerization reactions between the dosimeter and the contrast agent starting at 10 mg/mL, which compromised optical readings above 20 mg/mL. Omniscan consistently showed 37.7% lower sensitivity than standard PAGAT across all concentrations and dose levels. Conversely, Gadovist enhanced sensitivity by up to 50% at 20 mg/mL, with additional gains at higher concentrations, although accompanied by saturation at lower dose levels. Radiological analysis showed that all tested concentrations maintained mass energy–absorption coefficient differences below 1% and water-equivalence in effective atomic number within 5% at 6 MV. These findings underscore the importance of selecting an appropriate contrast agent to enhance gel dosimeter sensitivity, particularly in low-dose regions where measurement uncertainty increases. Additionally, gadolinium-infused PAGAT gels show strong potential for assessing dose enhancement phenomena. Their sensitivity, threshold behavior, and radiological properties suggest they may be suitable for applications in dose enhancement dosimetry as well as conventional clinical settings.